The law and politics of constitution making : lessons from Chile - Alema??n, Eduardo, 1969-; Soto Velasco, Sebastia??n (Comparative constitutional change., 2026)
"This collection examines Chile's two recent efforts to replace its constitution, both of which ultimately failed despite broad initial support. Drawing global media and scholarly attention, these high-profile processes offer critical lessons for understanding the challenges of democratic constitution making. The book features contributions from constitutional lawyers, political scientists, and other experts, including seven constitution writers, providing both academic analysis and firsthand accounts. It explores the institutional design of the constitution-making bodies, the influence of Chile's political context, the substantive proposals advanced in key policy areas, and the behavior of political actors and voters. It also offers insider evaluations of institutional and procedural choices that either supported or undermined the process. This volume is a key resource for scholars and policymakers interested in constitutional design, institutional reform, and Latin American politics. Readers in political science, constitutional law, and Latin American studies will find its analysis of Chile's process both informative and timely. Its interdisciplinary approach-blending comparative, legal, and empirical perspectives with practitioner insight-ensures broad relevance and appeal"-- Provided by publisher.